2012
DOI: 10.1357/002224012805262743
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling float-based and tracer-based estimates of lateral diffusivities

Abstract: Lateral diffusivities are computed from synthetic particles and tracers advected by a velocity field derived from sea-surface height measurements from the South Pacific, in a region west of Drake Passage. Three different estimates are compared: (1) the tracer-based "effective diffusivity" of Nakamura (1996), (2) the growth of the second moment of a cloud of tracer and (3) the single-and two-particle Lagrangian diffusivities. The effective diffusivity measures the cross-stream component of eddy mixing, so this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
137
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(155 citation statements)
references
References 35 publications
17
137
0
1
Order By: Relevance
“…Klocher et al, 2012b). To our best knowledge, though the effect of mean flow on tracer mixing induced by the total eddies has been studied (e.g.…”
Section: Diagnostic Frameworkmentioning
confidence: 99%
“…Klocher et al, 2012b). To our best knowledge, though the effect of mean flow on tracer mixing induced by the total eddies has been studied (e.g.…”
Section: Diagnostic Frameworkmentioning
confidence: 99%
“…where G denotes the O(1) mixing efficiency, u rms is the eddy velocity magnitude, and k denotes the eddy diffusivity (e.g., Taylor 1915;Klocker and Abernathey 2014). Bates et al (2014) pointed out that ocean studies often assume that L mix is of the same order of magnitude as the eddy size (e.g., Holloway 1986;Haine and Marshall 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty in n depends crucially upon the number of drifters, analogous to the results of Klocher et al (2012). This work is the first to my knowledge to attempt to quantify uncertainty in Kpir.…”
Section: Estimating Uncertainty Of Kmentioning
confidence: 66%
“…As noted in the introduction, Klocher et al (2012) showed that the diffusivity computed from drifters in the Southern Ocean depends directly on the number of drifters used in the computation. We wish to know whether the number of drifters in the GOM is sufficient to discern spatial variability in n as well as the asymmetry in the K tensor.…”
Section: Error Estimates By Bootstrappingmentioning
confidence: 87%
See 1 more Smart Citation